El teletrabajo postpandemia: beneficios y retos - Batista Jiménez, Almudena; Peiro de la Rocha, Lucas (Pontificia Universidad Católica del Perú, 2023)
The implementation of remote working in Spain has been accelerated by the COVID-19 healthcare crisis. This situation, which has quickly become a reality, has given rise to significant legislative changes regarding post-pandemic remote working, which were undoubtably necessary given the few regulations that were in place. However, certain questions have arisen regarding interpretation which have yet to be fully resolved.This article analyzes the main benefits of working from home (such as flexibility and work-life balance), as well as its challenges for companies and workers. For example, the need to have timekeeping records, guarantee the right to digitally disconnect from work, ensure corporate control and occupational risk prevention. It also looks at some practical solutions that companies are applying.Finally, the article briefly examines the main features of international remote working and the legal issues involved in implementing it based on the current international regulations.

La implantación del trabajo a distancia en España se ha visto acelerada como consecuencia de la crisis sanitaria provocada por el COVID-19. Esta realidad -impuesta a marchas forzadas- ha dado lugar a importantes modificaciones legislativas sobre el teletrabajo postpandemia, lo que, sin duda, era una necesidad dada la escasa regulación que existía. Sin embargo, también se han generado ciertas dudas interpretativas que a día de hoy continúan sin estar resueltas completamente.En el presente artículo se analizan los principales beneficios derivados del trabajo a distancia -tales como la flexibilidad y la conciliación-, así como los retos que se plantean para empresas y trabajadores, como son la necesidad de registrar la jornada laboral o de garantizar el derecho a la desconexión digital, el ejercicio del poder de control empresarial o a la prevención de riesgos laborales, citándose también algunas soluciones prácticas que se están aplicando por parte de las empresas.Por último, se examinan de forma sucinta las principales características del teletrabajo internacional y las dificultades jurídicas de su implementación sobre la base de la normativa internacional actual.
Post-pandemic remote working: benefits and challenge
Keywords: Remote working; Working from home; International; Balance; Timekeeping, digital disconnection; Corporate control; Occupational risk prevention; Trabajo a distancia; Teletrabajo; Internacional; Conciliación; Registro de jornada; Desconexión digital; Control empresarial; Prevención de riesgos laborales; https://purl.org/pe-repo/ocde/ford#5.05.00